Simulation and optimization of propane autothermal reformer for fuel cell applications - Insiong, Henry (2006)
Autothermal reforming (ATR) is one of the leading methods for hydrogen production from hydrocarbons. Liquefied petroleum gas, with propane as the main component, is a promising fuel for on-board hydrogen producing systems in fuel cell vehicles and for domestic fuel cell power generation devices. In this research, autothermal reforming of propane process is studied and operation conditions were optimized using Aspen HYSYS 2004.1 for proton exchange membrane fuel cell application. Furthermore, heat integration process also applied after the existed stream from the ATR reactor. Besides that water gas shift (WGS) which included High Temperature Shift (HTS), Medium Temperature Shift (MTS) and Low Temperature Shift (LTS) reactor, preferential oxidation (PrOx) were used for the clean up system to reduce the concentration of carbon monoxide. Then, optimization for the ATR, WGS and PrOx reactor were done to get the highest hydrogen produced with the lowest CO. Temperature and component’s profile were also investigated for every unit’s operations. Based on the final result, 100 kgmole/hr or propane with the ratio of air and water 1 : 7 : 4.3, produced 41.62% of hydrogen with CO concentration lower than 10 ppm, and 83.14% fuel processor efficiency.